Playing I Learn Digital Classroom: Innovating the Teaching of English Communication Skills - Ledesma Espin, Carmen del Rocio (2024)
The use of resources for digital education provides a favorable environment for students to practice and acquire a second language quickly and effectively. The objective of this educational study was to demonstrate that the implementation of digital educational resources improves English communicative skills in basic education students, Ecuador, 2023. A quasi-experimental methodology with a quantitative approach was used, using 80 students as the study population. The pretest results indicated slightly superior performance in the experimental group in all evaluated categories, highlighting a 10% increase in the Listening category. Subsequently, a 'Program for the use of digital educational resources' was introduced to enhance communicative skills in English. The results of the subsequent phase revealed that the majority of the students in the sixth grade 'A' had Listening (97.50%) and Reading (95.0%) skills at intermediate levels. However, a significant need for improvement in Writing skills was identified, since more than 50% of the students were at the low level. In response to these findings, a didactic guide focused on the development of English writing skills was developed, supporting the continuous need to adjust and perfect educational approaches to meet the changing demands of language learning.